2018
DOI: 10.1021/acsnano.8b02040
|View full text |Cite
|
Sign up to set email alerts
|

Oxide–Carbon Nanofibrous Composite Support for a Highly Active and Stable Polymer Electrolyte Membrane Fuel-Cell Catalyst

Abstract: Well-designed electronic configurations and structural properties of electrocatalyst alter the activity, stability, and mass transport for enhanced catalytic reactions. We introduce a nanofibrous oxide-carbon composite by an in situ method of carbon nanofiber (CNF) growth by highly dispersed Ni nanoparticles that are exsoluted from a NiTiO surface. The nanofibrous feature has a 3D web structure with improved mass-transfer properties at the electrode. In addition, the design of the CNF/TiO support allows for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 45 publications
(146 reference statements)
2
23
0
Order By: Relevance
“…The lower ECSA loss may be attributed to the higher scan rate, leading to lower particle growth [33]. The ECSA loss of the present study may also be compared with that by Joen et al, suggesting ~70% ECSA loss during AST of Pt/C (40 wt.% Pt) for 6000 cycles at a scan rate of 100 mV/s between 1.0 and 1.6 V in 0.5 M H2SO4 [34]. Fig.…”
Section: Typical Degradation Patternssupporting
confidence: 71%
“…The lower ECSA loss may be attributed to the higher scan rate, leading to lower particle growth [33]. The ECSA loss of the present study may also be compared with that by Joen et al, suggesting ~70% ECSA loss during AST of Pt/C (40 wt.% Pt) for 6000 cycles at a scan rate of 100 mV/s between 1.0 and 1.6 V in 0.5 M H2SO4 [34]. Fig.…”
Section: Typical Degradation Patternssupporting
confidence: 71%
“…To alleviate the negative effects of the amorphous carbon deterioration, corrosionresistant carbon supports; CNT [7,8], CNF [9], and graphene [10,11], heteroatom doped carbon [12] and also metal oxide supports have been introduced in the literature [13][14][15][16][17][18]. Among varied metal oxides [19][20][21], TiO 2 draws prominent attention because of high chemical-durability and good corrosion-resistance under PEFCs operation. In addition, the hypo d-electron character of TiO 2 enables its interaction with Pt, known as a strong metal support interaction (SMSI), thus changing the catalytic activity of the noble metal [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the calculation of density functional theory, TiO 2 has been considered as one of the most promising catalyst supports. The experimental results demonstrated that the strong metal-support interactions between Pt and TiO 2 can improve the catalytic performance [17] .…”
Section: Introductionmentioning
confidence: 93%
“…To reduce the dependence on precious metal and avoid the poisoning effect, catalyst supports consisting of carbon materials [7 , 8] and transition metal oxides (SiO 2 [9 , 10] , SnO 2 [11] , TiO 2 [12][13][14] , CeO 2 [15] are extensively studied. Among them, oxides play a critical role owing to their charge transfer phenomena [16] and the ability to inhibit the dissolution of Pt [17] . Based on the calculation of density functional theory, TiO 2 has been considered as one of the most promising catalyst supports.…”
Section: Introductionmentioning
confidence: 99%